(untitled) (Coordinates of Public Administration, 2026)
The article provides a comprehensive study of the institutional support for public governance of smart urban infrastructure development in the context of the digital transformation of public administration. It substantiates that the effectiveness of implementing Smart solutions in urban development is determined not only by the level of technological readiness or the availability of digital services, but primarily by the formation of a coherent institutional architecture capable of ensuring consistency of managerial decisions, coordination among public governance actors, and integration of digital tools into the system of strategic and program-based urban development. The multi-level structure of institutional support for Smart urban development at the national, regional, and local levels is analyzed, with an emphasis on the functional roles of central government authorities, local self-government bodies, and specialized development institutions. It is demonstrated that the national level establishes strategic, regulatory, and platform-based preconditions for digital transformation; the regional level ensures policy coordination and integration; while the local level serves as the key space for the practical implementation of smart infrastructure through project and portfolio management of territorial community development. Particular attention is paid to the analysis of digital platforms and systems as new institutional instruments of public governance. The role of the digital ecosystem of the Ministry of Digital Transformation of Ukraine in shaping the institutional and digital environment for smart urban infrastructure development is substantiated. It is proven that the combination of service-oriented, integration, and project-investment digital solutions creates the prerequisites for a transition from fragmented digitalization to systemic public governance of Smart development. The prospects for further research are identified and linked to substantiating the creation of a national Smart Cities platform as an open catalogue of solutions, projects, and governance models based on European practices. Such a platform would contribute to balancing the institutional and resource capacities of cities and ensuring the scaling of Smart solutions within a unified state policy for urban development.